2018
DOI: 10.19080/rapsci.2018.05.555671
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Energy Production from Rice Straw a Review

Abstract: Bio-Liquid Fuel Production from StrawOf the liquid fuels that may be produced from rice straw through liquid fermentation, bio ethanol fuel with its high oxygen content and octane no. is most important, but other compounds may also be advantageously produced from rice straw such as biobutanol and butanediol glycol. Rice straw is an especially attractive material for bio ethanol production although several challenges and limitations occur in the process of converting it to ethanol due to its high ash and silica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Presented data in Table (4) showed that, plants which cultivated in the clay soil and the old rice straw, 6 months treatments gave the highest values of plant diameter. Whereas, cultivated celery plants in new rice straw was obtained the lowest values of this parameter.…”
Section: Plant Diametermentioning
confidence: 94%
See 3 more Smart Citations
“…Presented data in Table (4) showed that, plants which cultivated in the clay soil and the old rice straw, 6 months treatments gave the highest values of plant diameter. Whereas, cultivated celery plants in new rice straw was obtained the lowest values of this parameter.…”
Section: Plant Diametermentioning
confidence: 94%
“…Data in Table (4) indicated that plant length was affected significantly by using different decomposition percentages of rice straw as a substrate. The greats values of plant length was obtained with clay soil treatment followed by old rice straw 6 months without any significant different between them.…”
Section: Plant Lengthmentioning
confidence: 99%
See 2 more Smart Citations
“…The same dam can also increase freshwater flows to promote rice farming in inland The Gambia during the prolonged dry season, thus serving multiple ecosystem benefits. From an energy perspective, different studies such as [58][59][60] have explored the potential of rice straw and rice husks as a potential feedstock for the production of biofuels to produce heat and electricity at household and micro-industry levels. This potential is minimally exploited in The Gambia despite its ability to transform the biofuels sector.…”
Section: Pathways Towards Wef Nexus Development Through Different Eba Practicesmentioning
confidence: 99%